Research into Spinal Deformities 7 - Aubin, Carl-Eric (IOS Press, 2013)
In choosing Montreal for its 8th biennial meeting, the International Research Society of Spinal Deformities (IRSSD), is returning to an auspicious and important venue: their 1992 meeting in Montreal marked the turning point from a focus on the morphological aspects of spinal deformity, towards three-dimensional evaluation and interpretation of scoliotic deformities and their biomechanics. Since then, the IRSSD meetings have had an instrumental role in the advancement of scientific research on problems affecting the spine. This book contains the proceedings of the 2010 conference in the form of peer-reviewed, short papers and abstracts, summarizing the 140 papers and posters presented at the Montreal meeting. With contributions from scientific and clinical experts from around the world, it covers all aspects of spinal deformity research including: etiology, genetics, biology, metabolism, biomechanics, imaging technologies, innovations in treatment and treatment outcomes. It explores current research developments, the underlying mechanisms that cause scoliosis and the clinical effectiveness of a wide range of treatments. Of interest to all those involved in the research into and treatment of spinal deformities, the book provides an opportunity to learn more about the latest developments in this field.